(untitled) (Orfeu, 2023)
This chapter focuses on the Sounds of Intent project, aimed mapping the musical development of young people with the most complex needs. From 2002, the research team worked with practitioners who were active in the field—music therapists, music educators, and other professionals—to develop accurate descriptions and shared interpretations of the different forms and levels of musical engagement they observed among children and young people with complex needs. The theoretical framework developed by the team is discussed in this translation.